Author correction: Necroptosis microenvironment directs lineage commitment in liver cancer - Seehawer, Marco; Heinzmann, Florian; D’Artista, Luana; Harbig, Jule; Roux, Pierre-François; Hoenicke, Lisa; Dang, Hien; Klotz, Sabrina; Robinson, Lucas; Doré, Grégory; Rozenblum, Nir; Kang, Tae-Won; et al. (Nature, 2018)
In this Article, the pCaMIN construct consisted of ‘mouse MYC and mouse NrasG12V’ instead of ‘mouse Myc and human NRASG12V; and the pCAMIA construct consisted of ‘mouse Myc and human AKT1’ instead of ‘mouse Myc and Akt1’ this has been corrected online.